Light-emitting diode street lights reduce last-ditch evasive manoeuvres by moths to bat echolocation calls - Wakefield, Andrew (R Soc Open Sci, 2015)
The light-emitting diode (LED) street light market is expanding globally, and it is important to understand how LED lights affect wildlife populations. We compared evasive flight responses of moths to bat echolocation calls experimentally under LED-lit and -unlit conditions. Significantly, fewer moths performed ‘powerdive’ flight manoeuvres in response to bat calls (feeding buzz sequences from Nyctalus spp.) under an LED street light than in the dark. LED street lights reduce the anti-predator behaviour of moths, shifting the balance in favour of their predators, aerial hawking bats.